Application of the fuzzy analytic hierarchy process in multi-criteria decision in noise action plans: Prioritizing road stretches. (July 2016) - Ruiz-Padillo, Alejandro; Torija, Antonio J.; Ramos-Ridao, A.F.; Ruiz, Diego P.
Abstract: Traffic noise is one of the major environmental impacts of road infrastructures. Critical study of published Noise Action Plans (NAP) signals a widespread lack of objective criteria and methodologies for prioritizing actions against noise as well as the suitability of solutions. The present paper develops a methodology to sort, by priority, road stretches included in a NAP. In obtaining and allocating weights to variables involved in the decision-making problem ("Road Stretch Priority Variables") to define a normalized numerical index ("Road Stretch Priority Index"), Fuzzy Analytic Hierarchy Process (FAHP) with two different defuzzification methods is applied to the results of an expert panel. Comparison of the outcomes of both FAHP versions, plus analysis of the results of a case study, enables to determine the relative influence of these variables in the problem. An objective and reasoned methodology for the prioritized classification of road stretches according to noise problems is thereby validated. Highlights: An advanced methodology is used to classify road stretches by priority for action. Fuzzy Analytical Hierarchy Process is employed to determine criteria weighting. Results from two defuzzification methods are compared in terms of consistency. Normalized and weighted variables are related in an objective and reasoned index. Relative influence analysis of the variables involved provides useful conclusions.